Obtaining good quality samples for cytology. Issue 4 (3rd May 2018) - Powell, Roger
Abstract : Cytology, or cytopathology, often requires the use of fine (less than 20 gauge) needle sampling to obtain cells to identify a pathological process. Alternatively, cells can be harvested via a direct impressed iatrogenic material or fluid preparation(s), via lavage or in‐vivo exfoliation into an effusion. Diagnosis of any pathology can be done with very few cells, but the more cells available, the more likely the correct diagnosis is made. To maximise chances of a correct diagnosis, cytology requires good quality samples, with detailed knowledge of normal and pathological cell features to examine the preparations. This article focuses on obtaining good quality samples with the principles being applicable to all veterinary species.